Air pollution and potential health risk in Ostrava region - a review - Jiřík, Vítězslav; Machaczka, Ondřej; Miturová, Hana; Tomášek, Ivan; Šlachtová, Hana; Janoutová, Jana; Velická, Helena; Janout, Vladimír (Central European Journal of Public Health, 2016)
AIM: The aim of this review was to collect all available data about air pollution in Ostrava, which is one of the most polluted area in central Europe and to make a concise assessment of health risks resulting from historical exposures of air pollutants since the beginning of the monitoring, i.e. since 1970 to the present time. METHODS: All available information sources (the Czech Hydrometeorological Institute, the Institute of Public Health in Ostrava or publications) were used. To evaluate the exposures both short-term (hourly and daily) data and long term (yearly) data during 45 years were analysed. For health risk assessment the relationship between exposure and biological effects of pollutants published by the WHO and the US EPA were employed. RESULTS: During the studied period annual average concentrations of PM10 ranged from 25 to 96 µg/m(3); PM2.5 from 24 to 45 µg/m(3); SO2 from 3.4 to 101.5 µg/m(3); NO2 from 17.76 to 51.17 µg/m(3); benzene from 0.24 to 9.2 µg/m(3); benzo[a]pyrene from 2.1 to 14 ng/m(3); arsenic from 1.2 to 9.5 ng/m(3). Since the turn of the 80s and 90s of the 20th century trend of air pollutant concentrations has been decreasing until the turn of millennium, when it stopped, and it has been constant until present time. However, presented results demonstrate that the citizens of Ostrava have been exposed to relatively high concentrations of pollutants in comparison to other similar cities. The most significant pollutants contributing to health risks are airborne dust (PM10, PM2.5), benzene and benzo[a]pyrene. The long-term average health risk of PM10 has increased in case of postneonatal infant mortality up to 30%; prevalence of bronchitis in children up to 61%; and incidence of chronic bronchitis in adults up to 89%. The long-term average health risk of PM2.5 increased for all-cause mortality in persons aged 30+ years up to 22%; cardiopulmonary related mortality up to 25%; and lung cancer related mortality up to 39%. The highest carcinogenic risk is observed in benzo[a]pyrene, when the range of individual lifetime carcinogenic risk is up to 1.25*10(-3). This assessment is valid according to the strict carcinogenic risk by the WHO, while the maximum carcinogenic risk according the US EPA is 7.2*10(-5). CONCLUSIONS: A significant reduction of the pollutants' concentrations in Ostrava in the nineties of the last century does not mean a required improvement of outdoor air quality to the desired level. Persisting episodes with a very strong short-term increase of the concentration of PM10 and PM2.5, as well as long-term load of these substances on the population is very high. Health risks from such burdens are likely to lead to a higher mortality and morbidity especially from specific diseases.
Keywords: látky znečišťující vzduch; Czech Republic; Environmental Monitoring; Humans; pevné částice; monitorování životního prostředí; Particulate Matter; lidé; Risk Assessment; Seasons; znečištění ovzduší; Česká republika; rizikové faktory; vystavení vlivu životního prostředí; Environmental Exposure; Air Pollutants; roční období; Risk Factors; Air Pollution; hodnocení rizik